Argyrosomus regius (Asso, 1801) fishery and ecology in portuguese waters, with reference to its relationships to other european and african populations - Prista, Nuno Miguel Guerra Geoffroy (2014)
Tese de doutoramento, Biologia (Biologia Marinha e Aquacultura), Universidade de Lisboa, Faculdade de Ciências, 2014